Antimicrobial resistance in Peru and Latin America - García Apac, Coralith (2012)
Antimicrobial resistance is a growing problem all over the world. In Latin America, important bacterial infections are now alarmingly beginning to increase their resistance to most available antibacterial agents. This means that bacteria are evolutionarily surviving and multiplying developing strains that are more difficult to treat, which may lead to the occurrence of severe diseases or death.